The dancer's guide and ball-room companion. (New York, Frank M. Reed, 1874)
This manual is a compilation of previously published materials. The guide begins with a brief description of the necessary arrangements for a ball, appropriate dress for men and women, and ballroom etiquette. The work continues with dances such as the quadrille, waltz, varsoviana, polka, schottisch, "Cellarius Waltz," and dances for larger groups of dancers--"Spanish Dance," "La Tempete," and "Sir Roger de Coverley."
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals